Student Participation in The Certified Internship and Independent Study Program (MSIB) and the Improvement of Soft Skills Among Students in Indonesia - Nurhayati, Riana; Tjiptasari, Fitriana; Saputri, Evi Rovikoh Indah (Journal of Nonformal Education, 2025)
The background of this study is the high unemployment rate among university graduates in Indonesia (842,378 people in 2024) due to the mismatch between competencies and industry needs. As a form of service learning, the Certified Internship and Independent Study Program (MSIB) is expected to improve students' soft skills. This quantitative study aims to measure the impact of MSIB on the overall improvement of students' soft skills and three specific aspects: communication skills, creativity, and conflict resolution. Data were collected through a Likert scale questionnaire from 118 MSIB participants at Yogyakarta State University and analyzed using simple correlation and MANOVA. The results show that 1) MSIB has a significant impact on the overall improvement of soft skills (12.1%); 2) MSIB has the most substantial impact on communication skills (50% variance), followed by creativity (37.4%), and conflict resolution (36.8%). These findings support the role of MSIB as an effective strategy in bridging the competency gap among graduates.